Measurement of agricultural productivity in Africa south of Sahara: A spatial typology application - Yu, Bingxin; Guo, Zhe (International Food Policy Research Institute, 2015)
The great diversity of agricultural activities and practices across the African continent has significant implications for technology transfer and productivity growth. This paper compiles diverse spatial data on biophysical conditions, farming systems, demographics, and infrastructure to spatially disaggregate country targets into subsystem units, namely agricultural production zones. The resulting typologies highlight the limitations of simple national aggregates and reveal remarkable heterogeneity in the subsystems within the country. The typologies provide a natural linkage between national-level analysis and localized production information and can help policymakers in refining national agricultural strategies through location- and subsystem-oriented policies based on local comparative advantages and constraints. The classification is useful in identifying commonalities beyond a country’s borders and hence encourages cross learning and joint efforts in scaling up policies.